Comparison of Proventriculus and Ventriculus Histology in Gallus Gallous Domestic us According to Food Composition - Fatemeh Soltani S arvestani (Journal of Global Pharma Technology, 2017)
The most important part of alimentary tract in digestion is proventriculus and ventriculus in poultry. Histology of these organs increasingly is affected by food composition. This study was carried out to investigate Histology of proventriculus and ventriculus with two different food compositions. One group was fed with natural food such as chopped vegetables and fruit and the other group fed with artificial food diet was provided from commercial company, for 8 weeks. Sections of proventriculus and ventriculus was provided and stained with hematoxilin and eosin routine method, histometric studies showed, there was significant increase in thickness of mucosa layer and number of adenomers in sub mucosa layer in proventriculus in group with natural food composition in compare to the other group. Moreover Thickness of mucosa layer and number of secretional crypts in sub mucosa layer and diameter of muscular layers in ventriculus showed remarkable increase in compare to the group with artificial food composition.Keywords: histology, Poultry, Diet